A man among other men : the crisis of Black masculinity in racial capitalism - Matlon, Jordanna (Cornell University Press, 2022)
"This book examines constructions of masculinity among men in the informal economy of Abidjan, Côte d'Ivoire. It demonstrates how French colonial legacies and global media representations of Blackness anchor identity and value within labor, consumerism, and commodification" --